Applying Supercritical Carbon Dioxide (ScCO\(_2\)) for Instant Rice Production - Mohammad Naghi Eshtiaghi; Nithima Nakthong (Scientific Research, New Technologies and Applications Vol. 9, 2024)
Rice is one of the most important foods for humans especially in Latin America and in Asian countries. In addition, rice is the most valuable for the fundamentals of the Thai economy. In order to produce instant rice, this study looked into the use of supercritical carbon dioxide (ScCO2). The efficiency of three pretreatment techniques—cooking, freezing, and ScCO2—in shortening the time required for rehydration and maintaining rice quality was compared. The findings demonstrated that the pretreatment of white and brown rice with ScCO2 at 600 bar notably reduced the amount of time needed for rehydration. Furthermore, the rice grains’ increased porosity as a result of the ScCO2 treatment aided in their quicker rehydration. This study highlights the potential of ScCO2 as a technology that could produce instant rice of superior quality and greater cooking convenience, benefiting the food industry as well as consumers.